Phylogeny, Phytomedicines, Phytochemistry, Pharmacological Properties, and Toxicity of Croton gratissimus Burch (Euphorbiaceae) - Kirkland Dingili Magwilu; Joseph Mwanzia Nguta; Isaac Mapenay; Dorine Matara (Advances in Pharmacological and Pharmaceutical Sciences)
Croton gratissimus is an important plant in Africa setup and across the globe for its ethnomedicinal uses in managing a wide range of diseases. Its phylogeny, pharmacological properties, ethnomedicinal uses, phytochemistry, and cytotoxicity have been highlighted in various articles and journals. This review article aims to give a comprehensively overviewed literature about Croton gratissimus genus. Authentic literature sources such as books, peer reviewed articles, journals, theses, Google Scholar, Science Direct, and any other validated internet source have been used to develop this review. Croton gratissimus is richly found across different climatic zones because of its ability to adapt to various climatic conditions. It is mainly found in rocky hills as a scrub that is about 12–15 m tall. Its leaves are glossy, green on the top, and silvery underneath. Some of the leaves may look brick red rusty. Croton gratissimus has been explored traditionally to manage a number of diseases among the human race since time immemorial. It has been used to treat different ailments ranging from respiratory tract infections, urinary tract infections, malaria, diabetes, hypertension, dermatological conditions, arthritis, gastrointestinal disorders, fever, sexually transmitted diseases, and infertility. Studies have shown that parts of this plant have antioxidative, antimicrobial, anticholinesterases inhibitory, antidiabetic, antihyperlipidemic, anticonvulsant, antiulcer, antihypertensive, antiproliferative, antiplasmodial, and anti-inflammatory activities. Terpenoids and flavonoids have shown to be the major classes of compounds in this plant. Its toxicity has not been well established; some studies have suggested that Croton gratissimus can cause hepatotoxicity and genotoxicity. More studies are needed to elucidate the compounds and their structures giving this plant a wide range of pharmacological activities, efficacy, safety, and toxicity levels, since the plant has greater ethnomedicinal uses. This would give a great indication of discovering new novelties that can give a breakthrough in drug discovery.